Emulsion Properties of Mixed Tween20-Span20 in Non-Aqueous System - Wan Mahamod, Wan Rusmawati; Kuang Abdulah, Dzulkefly; Lim, Wen Huei; Suhaimi, Mohd Hamdan (Universiti Putra Malaysia Press, 2002)
Oil-in-glycerol (O/G) emulsion was prepared in the presence of different weight ratios of mixed Tween20-Span20 surfactants. O/G emulsion was observed to form below 50 wt% of oil content at 3 wt% of mixed Tween20Span20 surfactants. Physical properties of the emulsion were determined by using a microscope, particle counting and rheological measurement. An attempt to correlate HLB values of mixed Tween20-Span20 with emulsion stability was also carried out.